2013
DOI: 10.1063/1.4823528
|View full text |Cite
|
Sign up to set email alerts
|

Cooling a low noise amplifier with a micromachined cryogenic cooler

Abstract: The sensitivity of antenna systems increases with increasing active area, but decreases at higher noise figure of the low-noise amplifier (LNA). Cooling the LNA locally results in significant improvement in the gain and in lowering the noise figure of the LNA. Micromachined Joule-Thomson (JT) coolers can provide a cryogenic environment to the LNA. They are attractive because they have no cold moving parts and can be scaled down to match the size and the power consumption of LNAs. The performance of a LNA mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This reduction in the size and mass of an antenna can be especially important in fasttracking systems, which require antennas to slew rapidly. Recent experiments have shown that cooling the LNA to 115 K can allow the antenna area to be reduced by about 43% [162].…”
Section: Uses For Optical Refrigeratorsmentioning
confidence: 99%
“…This reduction in the size and mass of an antenna can be especially important in fasttracking systems, which require antennas to slew rapidly. Recent experiments have shown that cooling the LNA to 115 K can allow the antenna area to be reduced by about 43% [162].…”
Section: Uses For Optical Refrigeratorsmentioning
confidence: 99%
“…The application potentials of a microcooler coupled with electronic devices has been demonstrated by cooling an yttrium barium copper oxide film through its superconducting phase transition by using a 30 K two-stage microcooler [100]. The utilization of the microcooler in cooling a low noise amplifier (LNA) was investigated by using a 115 K single-stage microcooler [101]. The performance of an antenna system can be improved by cooling the LNA stage in order to reduce its noise figure.…”
Section: University Of Twentementioning
confidence: 99%
“…Alternatively to large cryogenic Helium coolers, like GM or Stirling coolers, Nitrogen micro coolers have been developed [99]. In this concept high pressure Nitrogen (80-120 bar) flows through micro channels in a Silicon substrate before expanding in the tip, cooling that area, and being transported back to a separate compressor.…”
Section: Micro Coolingmentioning
confidence: 99%